Do Teachers Feel Valued in Society? Occupational Value of the Teaching Profession in OECD Countries - Motoko Akiba; Soo-yong Byun; Xiaonan Jiang; Kyeongwon Kim; Alex J. Moran (AERA Open, 2023)
Teacher accountability reforms implemented around the globe have heightened a sense that teachers are losing the support of policymakers and the general public. To examine the global pattern in teachers’ perception of occupational value and identify possible outcomes and predictors, we analyzed the 2018 Teaching and Learning International Survey (TALIS) data. We found an overwhelming majority of teachers feel undervalued in almost all OECD countries. In addition, teachers who feel undervalued reported less collective teacher effort for school improvement and job dissatisfaction consistently in four countries of comparison with different policy contexts—the United States, Australia, Finland, and Korea. However, the relationships between three working conditions impacted by accountability reforms—compensation, classroom autonomy, and involvement in school decision-making—and perceived occupational value varied across these four countries. Specifically, these working conditions seem to matter more in the United States, where the teacher policy context produces greater disparities across schools in teacher qualifications, distribution of qualified teachers, and degree of professional control.